(untitled) (American Journal of Islam and Society, 2010)
More than thirty years ago, the first World Conference on Muslim Education embarked upon the “Islamization of Knowledge,” a process articulated and expounded upon by the late Ismail Raji al-Faruqi (Temple University) and Naguib al-Attas, retired (ISTAC, Malaysia). The organizers of this conference, the seventh in this series, hoped to continue in this spirit by aiming “to be as dynamic and as influential as its predecessors” and to develop themes discussed in earlier conferences by locating them within “the current globalized atmosphere.” Moreover, it “expected to usher in a new era of Muslim education which will counteract the negative effects of globalization…” The organizers listed three special themes: “Curriculum for Muslim Education,” “Making Basic Teachings of Islam Relevant,” and “Religion and Youth” and twelve subthemes, among them “Integration of Knowledge,” “Madrasah Education,” “Quality of Muslim Education,” “Non- Muslim Perspectives on Muslim Education,” and “Principles of Critical and Creative Thinking in Muslim Education.” They also invited particular individuals to present papers, such as Wahbah Zuhayli (dean, Faculty of Islamic Law, University of Damascus [Syria]), Anis Ahmad (Riphah International University [Pakistan]; editor, The Quarterly Journal of the West & Islam), and Alparslan Acikgenc (Fatih University [Turkey]). Since the conference covered a variety of keynote speeches, presentations by well-known Malaysian scholars such as Osman Bakar (International Institute of Advanced Islamic Studies, Malaysia) and Kamal Hassan (International Islamic University Malaysia) and parallel sessions, I will comment briefly on the sessions and more extensively on some of the keynote speeches that set the tone for the discussions at the conference ...